2016
DOI: 10.1055/s-0042-101168
|View full text |Cite
|
Sign up to set email alerts
|

ABC3 Consensus Commented from the Perspective of the German Guidelines

Abstract: !The Third International Consensus Conference for Advanced Breast Cancer ABC3 on the diagnosis and treatment of advanced breast cancer was held in Lisbon from 5 to 7 November 2015. This year the focus was the treatment of metastatic breast cancer (stage IV) -including the patient perspectives. Important topics were questions relating to quality of life, the care for long-term survivors as well as the management of disease-related symptoms and treatment-based side effects. The use of standardised tools to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We therefore sought to augment the effect of KIFC1 depletion by combining it with a clinically relevant therapy capable of further induction of centrosome amplification in tumor cells. Platinum-based chemotherapies are currently considered one of the standard of care treatments for advanced TNBCs 37 and cisplatin is known to cause centrosome amplification by decoupling the centrosome duplication cycle from the DNA replication cycle 38 . We found that MDA-MB-231 cells show an increase in centrosome amplification when treated with increasing concentrations of cisplatin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore sought to augment the effect of KIFC1 depletion by combining it with a clinically relevant therapy capable of further induction of centrosome amplification in tumor cells. Platinum-based chemotherapies are currently considered one of the standard of care treatments for advanced TNBCs 37 and cisplatin is known to cause centrosome amplification by decoupling the centrosome duplication cycle from the DNA replication cycle 38 . We found that MDA-MB-231 cells show an increase in centrosome amplification when treated with increasing concentrations of cisplatin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In current clinical practice, approximately half of the patients with de novo stage IV disease were treated with local surgery, because it was associated with better local control and longer survival times in retrospective studies (19,25,26). The consensus from the Third International Consensus Conference for Advanced Breast Cancer suggests that surgery to the primary site can be considered in selected patients, particularly to improve the quality of life (27). However, the survival benefit of radiotherapy in these patients has been rarely investigated (13,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70-80% of patients with breast cancer are diagnosed with hormone receptor (HR)-positive luminal A or luminal B subtype. Endocrine therapy is an important treatment approach for hormone receptor-positive patients; yet, some patients may develop primary and secondary resistance (2)(3)(4). Endocrine resistance seems to be associated with the activation of multiple growth factor signaling pathways.…”
Section: Introductionmentioning
confidence: 99%